Dynamic Rocking Behavior Of Freestanding Symmetrical Rigid Blocks Considering Dynamic Soil-Structure Interaction - Jaimes, M. A.; Fernández-Sola, L. R.; Fernández-Sola, L. R.; Arredondo, C.; Arredondo, C.; Reinoso, E.; Reinoso, E. (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
We propose a dynamic model for the estimation of the rocking and overturning response for freestanding symmetrical rigid blocks, located in different storeys of a building under seismic action, considering the rotational component due to dynamic soil-structure interaction (DSSI). With this model, the influence of the soil-structure interaction on the dynamic behavior for rigid blocks is studied. An illustrative example of its application is presented for symmetric rigid blocks into buildings of 5, 10 and 15 floors located in soft soil of Mexico City. Results show that is important to consider both kinematic and inertial effects of DSSI on the dynamic response of contents. It is shown that the influence of these effects is more representative, as expected, for upper building levels.